Prevalence and Characteristics of Physiological Gaze-Evoked and Rebound Nystagmus: Implications for Testing Their Pathological Counterparts - Ritter, Michelle Sari; Bertolini, Giovanni; Straumann, Dominik; Bögli, Stefan Yu (Frontiers in Neurology, 2020)
Objective: Cerebellar diseases frequently affect the ocular motor neural velocity-to-position integrator by increasing its leakiness and thereby causing gaze-evoked nystagmus (GEN) and rebound nystagmus (RN). Minor leakiness is physiological and occasionally causes GEN in healthy humans. We aimed to evaluate the characteristics of GEN/RN in healthy subjects for better differentiation between physiological and pathological GEN/RN. Methods: Using video-oculography, eye position was measured in 14 healthy humans at straight ahead eye position before and after, and during 30s of ocular fixation at 4 horizontal eccentric targets between 30° and 45°. We determined the eye drift velocity and the prevalence of nystagmus before/during/after eccentric fixation. Results: Eye drift velocities during (range: 0.62±0.53°/s to 1.78±0.69°/s) and after eccentric gaze (range: 0.28±0.52°/s to 1.48±1.02°/s) increased with the amount of gaze eccentricity (30° to 45°). During continuous eccentric gaze, eye drift velocities decreased by 0.41±0.18°/s at 30°, and 0.84±0.38°/s at 45° gaze eccentricity. GEN was elicited in 71% of subjects at 30° gaze eccentricity. 21% showed RN thereafter. This prevalence increased to 100% (GEN)/72% (RN) at 45° gaze eccentricity. RN found after 30° gaze eccentricity was of low velocity (0.82±0.21°/s) and occurred after minor drift velocity decrease during prior eccentric gaze (0.43±0.15°/s). Conclusion: GEN and RN should be tested using horizontal gaze eccentricities of less than 30°, since most healthy subjects physiologically show GEN and RN at higher eccentricities. In case of an uncertain result, both the reduction of eye drift velocity during eccentric gaze and the velocity of RN can be analyzed to distinguish physiological from pathological nystagmus.